2015
DOI: 10.1080/15332667.2015.1041355
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Relational Marketing Bonds on Retailers' Economic and Social Satisfaction

Abstract: In the literature on channel relationships, there is a complex and hostile relationship between manufacturers and large retailers, especially given the growing strength of retail organizations in the global context. This study thus examines (a) the impacts of relational marketing bonds on economic and social satisfaction and (b) the role of economic satisfaction in the relationships between relational marketing bonds and social satisfactionin the manufacturer-retailer relationship. This quantitative study pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Previous studies which were conducted in other business contexts confirmed the aforementioned argument (Nath and Mukherjee 2012, Schakett et al 2011, Liang and Chen 2009a, Jonsson and Zineldin 2003, Mohd Noor, Perumal, and Goaill 2015. Therefore, this study claims that social bonds, which are developed between exchange partners positively influence the suppliers' satisfaction in the relationship with their trading partner.…”
Section: Conceptual Framework and Hypothesessupporting
confidence: 68%
See 4 more Smart Citations
“…Previous studies which were conducted in other business contexts confirmed the aforementioned argument (Nath and Mukherjee 2012, Schakett et al 2011, Liang and Chen 2009a, Jonsson and Zineldin 2003, Mohd Noor, Perumal, and Goaill 2015. Therefore, this study claims that social bonds, which are developed between exchange partners positively influence the suppliers' satisfaction in the relationship with their trading partner.…”
Section: Conceptual Framework and Hypothesessupporting
confidence: 68%
“…The findings are in agreement with previous research that examined the relationship between social bonds and satisfaction. In a study in the Yemeni manufacturer-retailer relationship, Mohd Noor, Perumal, and Goaill (2015) found out that social bonds are crucial in affecting retailers' satisfaction. Peltier and Scovotti (2005) sustained that social bond is the most influential factor of satisfaction in the healthcare marketing relationship.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations